2016
DOI: 10.1152/ajpendo.00468.2014
|View full text |Cite
|
Sign up to set email alerts
|

A 9-wk docosahexaenoic acid-enriched supplementation improves endurance exercise capacity and skeletal muscle mitochondrial function in adult rats

Abstract: Among the causes, modifications of the mitochondrial function could be of major importance. Polyunsaturated fatty (-3) acids have been shown to play a role in intracellular functions. We hypothesize that docosahexaenoic acid (DHA) supplementation could improve muscle mitochondrial function that could contribute to limit the early consequences of aging on adult muscle. Twelve-month-old male Wistar rats were fed a low-polyunsaturated fat diet and were given DHA (DHA group) or placebo (control group) for 9 wk. Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…Hess et al [64] reported that dietary algae and marine fish increase the levels of EPA and DHA in the equine skeletal muscles. Guen et al [65] reported that DHA-enriched supplementation improves endurance exercise capacity and skeletal muscle mitochondrial function in murine skeletal muscle. Stebbins et al [66] reported that DHA + EPA enhances skeletal-muscle blood and vascular conductance in active skeletal muscle (especially type I and IIa fibers) and that the increase in muscle blood is due to an increase in cardiac output secondary to increases in vascular conductance [66].…”
Section: Effects On Skeletal Musclesmentioning
confidence: 99%
“…Hess et al [64] reported that dietary algae and marine fish increase the levels of EPA and DHA in the equine skeletal muscles. Guen et al [65] reported that DHA-enriched supplementation improves endurance exercise capacity and skeletal muscle mitochondrial function in murine skeletal muscle. Stebbins et al [66] reported that DHA + EPA enhances skeletal-muscle blood and vascular conductance in active skeletal muscle (especially type I and IIa fibers) and that the increase in muscle blood is due to an increase in cardiac output secondary to increases in vascular conductance [66].…”
Section: Effects On Skeletal Musclesmentioning
confidence: 99%
“…DHA is an essential fatty acid that is ubiquitous in marine animals and plant plankton [ 9 ]. Previous studies have reported that the bioactivities of DHA, such as improvement in brain function [ 10 ], antitumor activity [ 11 ], regulation of lipid metabolism [ 12 ], regulation of glucose metabolism [ 13 ], anti-inflammatory effect [ 14 ], and improvement on exercise training and performance [ 15 ]. Increasing evidence also supports the beneficial effects of DHA on skeletal muscle function, such as alleviating muscular atrophy [ 16 ], ameliorating endurance exercise capacity [ 17 ], and contributing in recovery from exhaustion [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, EPA supplementation improved endurance exercise capacity and skeletal muscle mitochondrial function in adult rats 23) . Although we did not measure the mitochondrial function, EPA supplementation may improve not only mitochondrial content, but also respiratory function possibly via altering protein dynamics.…”
Section: Discussionmentioning
confidence: 96%